DETERMINAN STRUKTUR MODAL PERUSAHAAN FAMILY BUSINESS PADA INDEKS KOMPAS100 - Zayani, Salsabila Nada; Kristanti, Farida Titik (2021)
The purpose of this study was to determine the effect of the independent variables, as asset structure, growth opportunities, profitability, managerial ownership, firm size, and diversification with capital structure on family business in the KOMPAS100 Index for the 2014-2019 period. This study uses a quantitative approach to secondary data with a population originating from family business companies in the KOMPAS100 Index for the 2014-2019 period as many as 91 companies, purposive sampling technique was used in sampling, so that the total observations in this study amounted to 126 observations. The data analysis method used is panel data regression analysis, the data is processed using Eviews software. The results partially show that profitability, managerial ownership and diversification have an influence on capital structure. Meanwhile, asset structure, growth opportunities and firm size do not affect the capital structure. The results of the study simultaneously show that asset structure, growth opportunities, profitability, managerial ownership, firm size, and diversification have an influence on capital structure.